Neuronal Ndst1 depletion accelerates prion protein clearance and slows neurodegeneration in prion infection. - Patricia Aguilar-Calvo; Adela Malik; Daniel R Sandoval; Christopher Barback; Christina D Orrù; Heidi G Standke; Olivia R Thomas; Chrissa A Dwyer; Donald P Pizzo; Jaidev Bapat; Katrin Soldau; Ryotaro Ogawa; et al. (PLoS Pathogens)
Select prion diseases are characterized by widespread cerebral plaque-like deposits of amyloid fibrils enriched in heparan sulfate (HS), a abundant extracellular matrix component. HS facilitates fibril formation in vitro, yet how HS impacts fibrillar plaque growth within the brain is unclear. Here we found that prion-bound HS chains are highly sulfated, and that the sulfation is essential for accelerating prion conversion in vitro. Using conditional knockout mice to deplete the HS sulfation enzyme, Ndst1 (N-deacetylase / N-sulfotransferase) from neurons or astrocytes, we investigated how reducing HS sulfation impacts survival and prion aggregate distribution during a prion infection. Neuronal Ndst1-depleted mice survived longer and showed fewer and smaller parenchymal plaques, shorter fibrils, and increased vascular amyloid, consistent with enhanced aggregate transit toward perivascular drainage channels. The prolonged survival was strain-dependent, affecting mice infected with extracellular, plaque-forming, but not membrane bound, prions. Live PET imaging revealed rapid clearance of recombinant prion protein monomers into the CSF of neuronal Ndst1- deficient mice, neuronal, further suggesting that HS sulfate groups hinder transit of extracellular prion protein monomers. Our results directly show how a host cofactor slows the spread of prion protein through the extracellular space and identify an enzyme to target to facilitate aggregate clearance.